LEGAL EFFECT OF EXCEPTIONS TO THE RULES - Larina, Elena; Lapaev, Ivan; Popovicheva, Maria (Revista Inclusiones, 2020)
The purpose of the study is to provide a theoretical understanding of the essence of the phenomenon of legal force of exceptions to the rules, to reveal its content and to analyze the value and versatility of existing legal relations in Russian legislation. For the phenomenon of legal force of normative legal acts, the general rule is the hierarchy, as well as features of the acquisition and loss of legal force. The exception to these rules is retroactivity of the law, elimination of the punishability of the act or mitigation of punishment and ultra-activity of the law. The main exceptions to the rules are typical for the validity of a legal act over time. The analysis of exceptions to the rules is necessary because of the versatility and multi-aspect nature of existing legal relations, revealing their complexity, necessity and characteristic exceptions for each branch, both in public law and private legal relations. Conclusion: the principle "the law has no retroactive effect" is not one of the legal axioms.